THE HERO'S ROLE IN CREATING PERIOD REALITY IN OTKIR HASHIMOV'S STORIES (Conferencea, 2024)
This article discusses the analysis of the best short stories of O'tkir Hashimov and the role of the hero in creating the reality of the time in them. The writer's ability to create an artistic image in stories is analyzed.